2020
DOI: 10.1371/journal.pcbi.1008241
|View full text |Cite
|
Sign up to set email alerts
|

Models of SIV rebound after treatment interruption that involve multiple reactivation events

Abstract: In order to assess the efficacy of novel HIV-1 treatments leading to a functional cure, the time to viral rebound is frequently used as a surrogate endpoint. The longer the time to viral rebound, the more efficacious the therapy. In support of such an approach, mathematical models serve as a connection between the size of the latent reservoir and the time to HIV-1 rebound after treatment interruption. The simplest of such models assumes that a single successful latent cell reactivation event leads to observabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…Our results suggest that antibodies play a dual role, altering both the outcome of a latent cell activation, and the speed with which plasma viremia crosses the detection threshold. Interestingly, a larger latent reservoir is associated with a shorter delay between activation and detectable viremia, suggesting that after the successful activation occurs, there are subsequent activations that contribute to overall viremia during this stochastic phase, consistent with model predictions for SIV in van Dorp et al (2020) [44].…”
Section: Models That Best Explain the Datasupporting
confidence: 81%
See 1 more Smart Citation
“…Our results suggest that antibodies play a dual role, altering both the outcome of a latent cell activation, and the speed with which plasma viremia crosses the detection threshold. Interestingly, a larger latent reservoir is associated with a shorter delay between activation and detectable viremia, suggesting that after the successful activation occurs, there are subsequent activations that contribute to overall viremia during this stochastic phase, consistent with model predictions for SIV in van Dorp et al (2020) [44].…”
Section: Models That Best Explain the Datasupporting
confidence: 81%
“…Our model predicts that larger latent reservoir sizes are associated with shorter delay times between successful activation and detectable viremia, which suggests that the latent reservoir has some impact on the net growth rate of viral loads during rebound. We conjecture that this effect may be associated with secondary activations contributing to viral load as in Van Dorp et al (2020) [44]. This is also supported by experimental observations: for example, experiments where treatment interruptions were conducted on macaques that had been infected with a genetically barcoded SIV strain indicated that a significant number of cells could reactivate successfully from the latent reservoir [35].…”
Section: Groupsupporting
confidence: 80%
“…Presumably, the reservoir would similarly continue to decay post-ATI but pre-rebound, since the viral load remaining undetectable implies that robust viral replication, which may replenish the reservoir, is unlikely. Further, we recently showed that short-term viral rebounds are actually better explained by multiple successful latent cell activations in succession, with detectable viraemia composed of virus arising from replication in multiple lineages [56]. Lastly and importantly, we completely neglected the inherent heterogeneity of the latent reservoir.…”
Section: Exponentially Decaying A(t) Explains Both Short-and Long-term Viral Reboundmentioning
confidence: 99%
“…Several models have been proposed to explain the mechanisms behind viral rebound following ATI. The studies by Hill et al [35,36], Pinkevych et al [37,38], Fennessey et al [39], and van Dorp et al [40] hypothesized rebound as a stochastic process due to the reactivation of latently infected cells that release virus and initiate a chain of other successful infection events. Yet, in PTC, viral load is kept at a low level despite a large reservoir size in some people.…”
Section: Introductionmentioning
confidence: 99%